Psychological Distress and Sexual Dysfunction Among Premenopausal, Perimenopausal and Postmenopausal Women (The Journal of Cultural Perspectives, 2024)
In Pakistan, when it comes to women’s health and sexuality, traditional social and cultural practices often apt for modesty and discretion. Menopause is not even recognized as a health issue by even women themselves. Menopause, in Pakistan is usually marked out and stigmatized. Women going through menopause, most of the time cannot contemplate the phase, due to lack of knowledge and support, social isolation and unmet medical assistance. Another superior taboo, held in Pakistan, that requires serious attention is sexual dysfunction. Lack of awareness and education regarding their sexuality, in Pakistan, immensely leads women towards sexual health issues. Menopause and sexual dysfunction combined, pave path for psychological distress. Untreated menopause and sexual dysfunction can trigger psychological effects, such as stress, anxiety, and depression. Therefore Pakistan, is in a dire need of breaking these taboos, establish prevention plans, and implement awareness programs, in order to achieve well-being of women in health sector precisely.